1988
DOI: 10.1038/332800a0
|View full text |Cite
|
Sign up to set email alerts
|

A subfamily of stress proteins facilitates translocation of secretory and mitochondrial precursor polypeptides

Abstract: Depletion of a subset of 70K stress proteins in yeast mutants shows that they are involved in the post-translational import of precursor polypeptides into both mitochondria and the lumen of the endoplasmic reticulum. The identification of such a basic function may explain the remarkable evolutionary conservation of the gene family encoding these proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
763
1
8

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,470 publications
(792 citation statements)
references
References 49 publications
20
763
1
8
Order By: Relevance
“…They serve important functions when the microorganism adapts to environmental changes and their synthesis markedly increases when the cell is exposed to elevated temperatures or to other stress factors, such as oxygen radicals or ethanol. These proteins are believed to function intracellularly as molecular chaperones involved in protein folding, unfolding and assembly; in eucaryotes more precisely in protein unfolding before secretion [153]. The crystal structure of GroES from M. leprae has recently been elucidated and revealed a heptamer configuration with the form of a highly charged dome [154].…”
Section: Culture Filtrate Proteinsmentioning
confidence: 99%
“…They serve important functions when the microorganism adapts to environmental changes and their synthesis markedly increases when the cell is exposed to elevated temperatures or to other stress factors, such as oxygen radicals or ethanol. These proteins are believed to function intracellularly as molecular chaperones involved in protein folding, unfolding and assembly; in eucaryotes more precisely in protein unfolding before secretion [153]. The crystal structure of GroES from M. leprae has recently been elucidated and revealed a heptamer configuration with the form of a highly charged dome [154].…”
Section: Culture Filtrate Proteinsmentioning
confidence: 99%
“…Recently, it has been reported that an enzymatic unfolding activity is necessary for the denaturation of native proteins that are to be translocated across microsomal [11,12] and mitochondrial [11,19] membranes. This activity has been attributed to a member(s) of the 70 kDa heat shock protein family (hsp 70).…”
Section: Resultsmentioning
confidence: 99%
“…Although this process is well characterized [1][2][3], the machinery involved is not. In addition to the mitochondrial receptor/translocation apparatus and processing proteases, there is evidence suggesting that soluble cytosolic proteins are required as well [4][5][6][7][8][9][10][11]. It may be that an import-competent conformation effected by soluble proteins results in the enhanced translocation of proteins across both microsomal [11][12][13], mitochondrial [11] and bacterial cell membranes [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a function is illustrated by the reactivation of heat-denatured and aggregated E. coli RNA polymerase in the presence of ATP and DnaK protein, the bacterial hsp70 (Skowira eta/., 1990). In cells grown under normal conditions, constitutive hsp70s have been shown to bind protein precursors and to maintain them in a proper conformation during protein transport and secretion (Deshaies et a/., 1988). For example, genetical and biochemical evidence have demonstrated that hsp70s are involved in the transport of proteins into yeast mitochondria (Kang et a/., 1990).…”
Section: Introductionmentioning
confidence: 99%